2015
DOI: 10.1111/edt.12203
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of mandible fracture in children under 12 years in a district trauma center in India

Abstract: In addition to factors such as age, gender, etiology, anatomic site, and treatment of mandibular fracture, this study also reported statistics regarding other factors such as residing area, socioeconomic status, and interval from trauma to reporting in Indian patients. It is hoped that the data presented here will be valuable to the government agencies and healthcare professionals for planning treatment, recommending preventive measures and encouraging research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
5
9
0
Order By: Relevance
“…Falls from height (44.9%) were the major cause of mandibular fracture in this study. Our results are in agreement with the observations of Collao-González et al5, Joshi et al8, Namdev et al16, Owusu et al17, Kumaraswamy et al18, and Atilgan et al19, who also reported that falls from height were the most common mechanism of maxillofacial trauma in children. In this study, more than half of the population in Group A and Group B sustained mandibular fractures due to falls from height, representing low velocity/energy trauma.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Falls from height (44.9%) were the major cause of mandibular fracture in this study. Our results are in agreement with the observations of Collao-González et al5, Joshi et al8, Namdev et al16, Owusu et al17, Kumaraswamy et al18, and Atilgan et al19, who also reported that falls from height were the most common mechanism of maxillofacial trauma in children. In this study, more than half of the population in Group A and Group B sustained mandibular fractures due to falls from height, representing low velocity/energy trauma.…”
Section: Discussionsupporting
confidence: 94%
“…The results of this study support the finding of a study by Namdev et al16, who also observed the majority of mandibular fracture cases in rural areas. Poor road conditions in some parts of rural India, especially during the rainy season, may have contributed to an increased incidence of maxillofacial trauma.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3,5,6 The mandible is the only mobile facial bone and in cases of injury to the maxillofacial region it is more vulnerable than the mid-face to fractures. 7 Depending on the direction and force of the trauma, fractures of the mandible frequently occur at different sites. 7 The most commonly fractured areas are the body (29%), followed by the condyle (26%), angle (25%), and symphysis (17%), while the ramus (4%) and coronoid process (1%) are rarely fractured.…”
Section: Introductionmentioning
confidence: 99%
“…7 Depending on the direction and force of the trauma, fractures of the mandible frequently occur at different sites. 7 The most commonly fractured areas are the body (29%), followed by the condyle (26%), angle (25%), and symphysis (17%), while the ramus (4%) and coronoid process (1%) are rarely fractured. The most common causes of fractures to the condyle, symphysis and angle include car accidents, motorcycle accidents, and physical assault respectively.…”
Section: Introductionmentioning
confidence: 99%